KEEFEKTIFAN MEDIA PEMBELAJARAN WHATSAPP DALAM PEMBELAJARAN DARING DI MI FASTABIQUL KHOIROT - Sasabila, Luthfi Adinda (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2024)
Abstract. This study aims to (1) find out how the implementation of online learning at the Islamic Elementary School Fastabiqul Khoirot using WhatsApp learning media, (2) find out the opinions of teachers and parents regarding online learning using learning media in the form of WhatsApp, 3) determine the effectiveness and feasibility of the media. This WhatsApp learning is for daily learning. In this study, researchers used field research with descriptive qualitative methods which were carried out at the Fastabiqul Khoirot Islamic Elementary School. The data obtained based on interviews from the head of the Islamic school were also various opinions of parents who were obtained from various complaints submitted to the principal of the Islamic school as well as the educators at the Islamic school. Based on the results of the research, namely 1) the implementation of online learning at the Islamic elementary school Fastabiqul Khoirot by utilizing the WhatsApp application as a learning medium is certainly quite helpful so that online learning can continue to be implemented. 2) Based on the opinion of the head of the Islamic school, online learning that uses learning media in the form of WhatsApp is quite helpful in order to keep the implementation of online learning even though there are still some obstacles that it causes, while the parents themselves also think that they agree more if online learning is carried out through the WhatsApp application media. because the application is considered more flexible, efficient in reducing quotas compared to other applications, it is also easy to operate 3) Although the use of online learning media in the form of the Whatsapp application still has some obstacles, its use is quite effective and also feasible as an online learning medium for Islamic elementary school .